(untitled) (Cambridge, England, 2000)
Productivity and its determinants is a prominent feature in economic debate. Output per person or per capita is still the most influential measure of the prosperity of nations. Productivity depends on the quantity and quality of the factors of production available to a country and the social framework within which they operate. Education and the research base affect both the quality of factors and the ability of a nation to produce. This volume examines differences in productivity between nations, and provides comprehensive discussion as to why such differences exist; it addresses the importance of the growth and measurement of service productivity, and studies the role of human capital in adapting to new technologies. The creation of knowledge through research and development and its diffusion through trade, investment and the interaction of firms are also fully investigated.
Keywords: Technological innovations,Economic policy,Đổi mới công nghệ,Chính sách kinh tế; Economic aspects,Khía cạnh kinh tế